Pacific Lamprey drag force modeling to optimize fishway design. Issue 1 (2nd January 2021) - Zobott, Hattie; Budwig, Ralph; Caudill, Christopher C.; Keefer, Matthew L.; Basham, William
Abstract: Typically, fish passage design is informed by a critical velocity model whereby fish are assumed to fail passage if the water velocity is higher than the critical swim speed, an assumption that may not be met when locomoting fish are partially submerged. We applied a drag force model (DFM) approach for use in design of Pacific Lamprey ( Entosphenus tridentatus ) Passage Structures (LPS) where lamprey may be partially or fully submerged. Our investigation assessed the dead-drag forces at four levels of static submergence: fully submerged (120 mm), equally submerged (40 mm), partially submerged (15 mm), and skin-flow (5 mm) for a Pacific Lamprey physical model by varying simulated LPS slope and discharge conditions. We then used the results to establish drag force thresholds corresponding to the known critical velocity thresholds of Pacific Lamprey to predict passage success under partial and full submergence conditions. Consideration of drag force in fish passage could be used to improve or create species-specific design recommendations for fishways, or to inform the design of barriers to prevent invasive species passage. The results suggest consideration of drag force in addition to velocity is beneficial to predict Pacific Lamprey passage success under partial submergence conditions.